THE EFFECT OF INTEREST RATE, INFLATION RATE AND RUPIAH EXCHANGE RATE ON INVESTMENT RESULTS IN SHARIA LIFE INSURANCE COMPANIES IN INDONESIA - Dimas Alif Putra; Juliana Juliana; Firmansyah Firmansyah; Ropi Marlina (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2023)
This study aims to analyze the effect of interest rates, inflation rates and the rupiah exchange rate on investment returns in Islamic life insurance companies in Indonesia in 2016 – 2020. The data collection in this study used secondary data obtained from the Islamic Non-Bank Financial Industry (IKNB Syariah), and Bank Indonesia. The research method used is quantitative with a causal approach. The analytical tools used are: Eviews software version 10. The results of this study indicate that: First, interest rates have a positive and insignificant effect on investment returns, second, inflation rates have a negative and significant effect on investment returns. Third, the Rupiah Exchange Rate has a negative and significant effect on investment returns. The implications of this research show that. The low interest rate in 2020 makes the decline in investment returns also decrease in 2020. In addition, the negative impact of the inflation rate on investment returns is because high inflation will increase the risk of investment returns, if the risk of investment returns is high, Islamic life insurance companies will transfer funds to other insurance instruments. As for the weakening of the rupiah exchange rate, insurance companies will reduce the allocation of capital to investment, if the allocation of investment capital decreases, it will reduce the investment returns they get.